Corporate Governance and Firm Performance: Empirical Evidence From Indonesia Stock Exchange (Kompas 100 Index) - Rahmah Putri Wijayanti (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The purpose of this study is to determine how the impact of corporate governance practices on the performance of companies that have go public in IDX, especially in the KOMPAS 100 index company. The proxies used in this study are boards directors, independent directors, and audit committee. While company performance is measured by ROA. This study uses annual report documents and financial reports from KOMPAS 100 index companies, starting from the period 2019 to 2023. The data analysis method used is multiple regression analysis.